Temperature dependence of the structural parameters of the non-oxide perovskite superconductor MgCNi3 - Huang, Q; He, T; Regan, K; Rogado, N; Hayward, M; Haas, M; Inumaru, K; Cava, R (2001)
We report the structural parameters of superconducting MgCxNi3 (x=0.96, Tc=7.3 K) as a function of temperature, from 2 to 295 K, determined by neutron powder diffraction profile refinement. The compound has the perovskite structure over the whole temperature range, with symmetry Pm3̄m and a=3.81221(5) Å at 295 K: no structural or long range magnetic ordering transitions were observed. The lattice parameter a and the Debye-Waller factors for the individual atoms decrease smoothly with decreasing temperature. There are no unusual changes of the structural parameters near Tc. © 2001 Elsevier Science B.V. All rights reserved.